Sustainable urban design : an environmental approach - Ritchie, Adam, MCIBSE; Thomas, Randall (London ; New York : Taylor & Francis, 2009)
"Towns and cities form the backdrop to the lives of a rapidly increasing number of people around the world. Sustainable Urban Design, 2nd Edition addresses the issues faced by planners and designers in making these areas environmentally sustainable."--BOOK JACKET
Includes bibliographical references (p. 222-229) and index
1
Keywords: City planning -- Environmental aspects; Sustainable development; Urban ecology (Sociology)